COVID-19 Pandemic Effect on Stress Levels and Sleep Patterns - Dirga Filannira Desky; Eka Roina Megawati; Christoforos Giannaki (Sumatera Medical Journal, 2024)
Background: Physical distancing during COVID-19 pandemic had important role to prevent and slow down its transmission but has some negative psychological effects such as stress, confusion, frustation, and sleep pattern changes. Objective: The aim of this study was to determine the effect of the COVID-19 pandemic on stress levels and sleep patterns. Methods: This was a cross sectional study that involved a hundred medical students of Universitas Sumatera Utara. The data of this study was obtained by questionnaires and analyzed using Spearman correlation test. Results: This study found that based on the stress level, there were 59 students categorized normal, mild 16 students, moderate 10 students, severe 9 students, and very severe 6 students. The sleep patterns described that only 11 students slept normally and 89 students experienced sleep disturbances during the COVID-19 pandemic. This study found there was a significant correlation between the COVID-19 pandemic on stress levels (p:0.01 and r:0.58) and sleep patterns (p:0.01 and r:0.36). Conclusion: This study found that the COVID-19 pandemic had a significant impact on increasing stress levels and causing sleep disturbances among medical students. Strengthening mental health support during pandemics is essential to minimize these effects.